Australian financial firms' exposures to the level, slope, and curvature of the interest rate term structure. Issue 19 (21st April 2017) - Akhtaruzzaman, Md.; Shamsuddin, Abul
ABSTRACT: This study examines the risk exposure of Australian financial firms to changes in the term structure of interest rates. Non-linearity in the interest rate term structure is captured by the three-factor model of interest rate level, slope, and curvature. We observe that financial firms have negative exposures to the interest rate level, while non-financial firms have positive exposures. This finding suggests that financial firms need to hedge against rising interest rates, while non-financial firms need to hedge against falling interest rates. Small banks and insurance companies have a positive risk exposure to the slope factor, while real estate firms have a negative risk exposure to the curvature factor. Though the interest rate level is the most important factor, ignoring the slope and curvature factors could lead to underestimating a financial firm's overall interest rate risk exposure. These findings are robust to controlling for the orthogonalized market return, time-varying equity risk premium, and the global financial crisis. This study offers practical tools to regulators, such as the Reserve Bank of Australia and Australian Prudential Regulatory Authority for assessing interest rate risk exposures of the financial and non-financial sectors.